Electrospinning of antibacterial scaffolds composed of poly (L-lactide-co-ε-caprolactone)/collagen type I/silver doped hydroxyapatite particles: potential material for bone tissue engineering. Issue 3 (24th February 2022) - Erdem, Ramazan; Yavuz, Emre; Akarsu, Esin; Akarsu, Murat; Yılmaz, Özlem Erdem; Coşgun, Ahmet
Abstract: In current study, various types of electrospun scaffolds have been prepared including poly(L-lactide-co-ε-caprolactone), collagen type I, hydroxyapatite nanoparticles (HAp) and silver doped hydroxyapatite particles (Ag-HAp). 13 C-NMR, 1 H-NMR, FT-IR, XRD, TEM and EDS analyses were performed to characterize the synthesized copolymer and nanoparticles. SEM analysis revealed that the greatest fiber diameter (761 ± 434 nm) was yielded for PLCL fibers, on the other hand, smallest diameter (151 ± 91 nm) was measured for PLCL/COL/Ag-HAp based fibers. According to contact angle test, the existence of collagen and HAp in the blend improved the hydrophilicity of the electrospun scaffolds. The highest tensile strength value (28 MPa) was determined for PLCL/COL based scaffold in the machine direction. Antibacterial efficiency of PLCL/COL/Ag-HAp scaffold was evaluated against gram-positive ( Staphylococcus aureus ) and gram-negative ( Escherichia coli ) bacteria and remarkable bactericidal effect (99.99%) has been recorded. Abstract : UF0001